Film and method for producing cured product using same

By using the inert oxidation reduction cause system to solidify the contact with solidified composition, the problem of high temperature or UV irradiation in the existing technology is solved, and the production of solidification products at room temperature can be used to avoid reduced pollution and physical characteristics. Question.

CN119384438APending Publication Date: 2025-01-28LG CHEM LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380046344.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-17
Filing Date
2023-06-16
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The prior art requires high temperature or UV irradiation when producing cured products, resulting in reduced physical characteristics of the device and problems of pollution caused by solvent volatility and gas generation.

Method used

A membrane that can be used for inert oxidation reducing preparation system, solidify the contact with the contact composition, avoids the use of high temperature or UVs alone, and achieves solidification at room temperature.

Benefits of technology

The production of curing products without high temperature or UV irradiation is achieved, avoiding pollution caused by reduced the physical characteristics of the device and the volatilization of the solvent, while maintaining the uniformity and the physical characteristics of the expectations of solidification products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119384438A_ABST
    Figure CN119384438A_ABST
Patent Text Reader

Abstract

The present invention relates to a film and a method for producing a cured product using the same, and in particular, to a film useful in an inert redox initiator system and a method for producing a cured product. Specifically, the film according to the present invention is characterized in that it comprises a substrate and an activation layer comprising an initiator component on the surface of the substrate, a curing reaction is performed when a layer of a curable composition comprising a curable slurry, a filler component, and an initiator component is brought into contact with the initiator component of the film, and the activation layer is formed on the surface of the substrate. And the initiator component is an inert redox initiator system comprising an oxidizing agent and a reducing agent, where the reducing agent comprises a metal compound, and the metal compound is included in an effective amount only in any one of the active layer of the membrane and the layer of the curable composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to films and methods of producing cured products using the same, and in particular, to films that can be used in inert redox initiator systems and methods for producing cured products. Background Art

[0002] In the past, solvent-based compositions have been mainly used as existing methods for producing cured products, wherein the solvent-based compositions substantially require high temperature or UV irradiation during a curing process (eg, a volatilization process of a solvent).

[0003] However, if necessary, a curing process may be performed after applying the composition required to form a cured product to a specific device, wherein the device to which the curable composition is applied is affected by high temperature or UV irradiation, thereby there may be a problem of reduced physical properties of the device. When forming a cured product in this way, there are cases where it is difficult to apply a high temperature or UV process.

[0004] Furthermore, solvent-based compositions cause pollution problems during the volatilization of the solvent and quality consequences due to gas generation.

[0005] In order to solve the above problems, a method of forming a cured product by minimizing the use of a solvent may also be considered, but it is a difficult task to achieve a cured product having physical properties similar to those of a solvent-based composition using a solventless composition. Summary of the invention

[0006] Technical issues

[0007] Therefore, the problem to be solved by the present invention is to provide a cured product that can be produced without applying a separate high temperature or UV process through a film that can be used for an inert redox initiator system, and a method for producing a cured product using the same. The technical problem of the present invention is not limited to the technical problem described above, and other technical problems that are not mentioned will be clearly understood by those skilled in the art from the following description.

[0008] Technical Solution

[0009] The present invention can make multiple changes and can have multiple examples, thus specific examples will be shown in the drawings and described in detail. However, these are not intended to limit the present invention to specific embodiments, and should be understood to cover all changes, equivalents and alternatives included in the spirit and technical scope of the present invention.

[0010] In the present specification, the term normal temperature or room temperature means a natural temperature without artificial heating or cooling, and may mean any temperature of about 10° C. to 30° C., preferably 23° C. to 27° C., depending on the season.

[0011] The terms used in this application are only used to describe specific examples, which are not intended to limit the present invention. Unless the context clearly stipulates otherwise, singular expressions include plural expressions. In this application, it must be understood that terms such as "including" or "having" are intended to indicate the presence of features, quantities, steps, operations, components, parts or combinations thereof described in the specification, but do not preclude the presence or possibility of adding one or more additional features, or quantities, steps, operations, components, parts or combinations thereof.

[0012] Unless otherwise defined, all terms (including technical or scientific terms) used herein have the same meaning as those generally understood by ordinary technicians in the field to which the present invention belongs. Unless explicitly defined in this application, terms such as those defined in commonly used dictionaries should be interpreted as having a meaning consistent with the meaning in the context of the relevant technology, and they are not interpreted as ideal or overly formal meanings.

[0013] In a specific example according to the present invention, the present invention may relate to a film. More specifically, the film of the present invention relates to an inert redox system that is matched with a layer of a curable composition, wherein the inert redox system is based on an inert redox initiator system. In this specification, "redox initiator system" means initiating free radical polymerization by a redox initiator at room temperature, and specifically, means initiating free radical polymerization by an electron transfer reaction according to the free radicals generated by the redox reaction of the initiator. In particular, the present invention uses an inert redox initiator system, wherein in this specification, "inert redox initiator system" means a redox initiator system that is formulated so that redox is not possible with only a single initiator component.

[0014] In one example, the film according to the present application may include a substrate and an activation layer including an initiator component on a surface of the substrate.

[0015] Substrate can be used without restriction, as long as activation layer can be applied to surface, but an example can include polymer, plastic, metal, wood, leather or concrete etc.The example of polymer substrate can include polymer based on cellulose acylate, cycloolefin polymer, polymer based on polycarbonate, polymer based on acrylate, polymer based on polyester, polymer based on polyimide etc., without being limited thereto.The example of plastic substrate can include polyethylene terephthalate (PET), polyether sulfone (PES), polycarbonate (PC), polyarylate (Par), cycloolefin copolymer (COC) etc., without being limited thereto.Metal substrate can include aluminum, copper, silver, iron, zinc, nickel, titanium and gold etc., without being limited thereto.

[0016] When a layer of a curable composition comprising a curable slurry, a filler component and an initiator component is brought into contact with the initiator component of the activation layer in the film, the film can undergo a curing reaction. Therefore, the film according to the present invention can have excellent storage characteristics, and provides a cured product that allows uniform overall curing when a curing reaction is carried out only by bringing the film into contact with a layer of a curable composition, because the surface of the film in contact with the curable composition is not only partially cured, but also almost no difference in the degree of curing occurs in the thickness direction of the film.

[0017] Meanwhile, in the present specification, "curable slurry" means a unit that forms a polymer in a final cured product by curing or crosslinking, which may include an oligomer formed by polymerizing two or more monomers, or a polymer component and a monomer component. As an example, the curable slurry may include a monomer, a (partial) polymer, and a crosslinking agent, wherein if the monomer component is partially polymerized into a (partial) polymer according to the desired composition, some of the monomers are polymerized to form an oligomer or a polymer, and the remaining monomers are retained, thereby constituting the curable slurry.

[0018] Therefore, in this specification, the term of the monomer unit such as the (meth)acrylate unit described below may mean a monomer present in the curable syrup in a state of forming an oligomer or a polymer, or a monomer that is not polymerized but contained in the curable syrup. Therefore, when the content of the curable syrup is calculated in this specification, it means that the syrup components include not only components that are in a monomer state and do not participate in polymerization, but also components that participate in polymerization.

[0019] Meanwhile, as described below, the oxidizing agent and the reducing agent as initiator components are only used to initiate polymerization by generating free radicals, but are not introduced into the final cured product for the purpose of forming polymer units, thereby distinguishing from the curable syrup, but some of the initiator components may also be present in the final cured product by bonding to the polymer.

[0020] In addition, in the present specification, the initiator component means a redox initiator, which may include an oxidant and a reductant. In the present specification, the oxidant and the reductant mean components that participate in or assist in generating free radicals that initiate polymerization by participating in or assisting in oxidation-reduction reactions under a redox initiator system.

[0021] The curable composition in the present invention comprises a curable syrup containing a monomer unit, a crosslinking agent and / or (partial) polymer, a filler component and an initiator, wherein the initiator is a concept covering a reducing agent and an oxidizing agent, and needs to be designed to have excellent solubility, compatibility, dispersion rate and reactivity between the components constituting the composition, without being limited thereto, but the following composition can be used in the present application.

[0022] In one specific example, the curable composition comprises a filler component. The term filler component means a component consisting of a filler, ie, a component comprising only a filler.

[0023] In one example, the filler component can include 2 or more types of fillers with different average particle diameters. In one example, the filler component can include 3 or more types of fillers with different average particle diameters, or can be composed of 3 to 6 types, 3 to 5 types, 3 to 4 types, or 3 types of fillers with different average particle diameters. That is, in one example, the filler component can also only include 3 to 6 types, 3 to 5 types, 3 to 4 types, or 3 types of fillers with different average particle diameters.

[0024] In another example, the filler component can show at least two peaks in the volume curve of the particle size distribution measured using the laser diffraction method. In an example, the filler component can show three or more peaks in the volume curve of the particle size distribution, or can show three to six peaks, three to five peaks, three to four peaks, or three peaks. For example, the range of filler components showing three peaks does not include filler components showing one, two, or four or more peaks.

[0025] The average particle size of the filler in the present application means the particle size at which the volume accumulation is 50% in the volume curve of the particle size distribution measured by the laser diffraction method, which may also be referred to as the median diameter. That is, in the present application, the particle size distribution is obtained on a volume basis by the laser diffraction method, and the particle size at the point where the cumulative value is 50% in the cumulative curve with the total volume set to 100% is set as the average particle size, wherein in another example, such an average particle size may be referred to as the median particle size or D 50 Particle size.

[0026] Therefore, here, two types of fillers having different average particle sizes may mean fillers having different particle sizes at a point where the cumulative value is 50% in a volume curve of particle size distribution.

[0027] Generally, when two or more types of fillers having average particle diameters different from each other are mixed to form a filler component, as many peaks as the types of the mixed fillers appear in the volume curve of the particle size distribution measured for the filler component using the laser diffraction method. Therefore, for example, when a filler component is formed by mixing three types of fillers having average particle diameters different from each other, the volume curve of the particle size distribution measured for the filler component using the laser diffraction method shows three peaks.

[0028] The filler component may be a thermally conductive filler component. The term thermally conductive filler component means a filler component that functions to allow the curable composition to be cured to exhibit thermal conductivity to be described below.

[0029] As an example, the curable composition of the present application may contain a filler component in an amount of 200 parts by weight or more relative to 100 parts by weight of the curable slurry. In another example, the filler component may be contained in an amount of 250 parts by weight or more, 300 parts by weight or more, 350 parts by weight or more, 400 parts by weight or more, 450 parts by weight or more, 500 parts by weight or more, 550 parts by weight or more, 600 parts by weight or more, 650 parts by weight or more, 670 parts by weight or more, 700 parts by weight or more, or 730 parts by weight or more relative to 100 parts by weight of the curable slurry, and the upper limit thereof is not greatly limited, but may be 1,500 parts by weight or less, 1,400 parts by weight or less, 1,300 parts by weight or less, 1,200 parts by weight or less, 1,100 parts by weight or less, 1,000 parts by weight or less, 900 parts by weight or less, or 800 parts by weight or less.

[0030] That is, according to the present application, the curable composition can exhibit excellent thermal conductivity by including a relatively excessive amount of a filler component and at the same time increasing the packing density by adjusting the particle size and / or ratio of the filler contained in the filler component, and can also provide a cured product that can be cured by a redox initiator at room temperature without any energy source such as separate UV or heat, and has desired physical properties.

[0031] The filler component included in the curable composition of the present application may satisfy the following General Formula 1.

[0032] [General formula 1]

[0033] 5≤D 50A / D 50C ≤100

[0034] In general formula 1, D 50A is the maximum average particle size of the filler component, and D 50C It is the minimum average particle size of the filler component.

[0035] Here, when the filler component contains two or more types of fillers having average particle diameters different from each other, the maximum average particle diameter (D 50A ) may refer to the average particle size of the filler having the largest average particle size among the fillers contained in the filler component. Alternatively, in another example, the maximum average particle size (D 50A) may mean a particle diameter of a peak appearing at a maximum particle diameter among peaks appearing in a volume curve of a particle size distribution measured for a filler component using a laser diffraction method.

[0036] Here, when the filler component contains two or more types of fillers having average particle diameters different from each other, the minimum average particle diameter (D 50C ) may refer to the average particle size of the filler having the smallest average particle size among the fillers contained in the filler component. Alternatively, in another example, the minimum average particle size (D 50C ) may mean a particle diameter of a peak appearing at a minimum particle diameter among peaks appearing in a volume curve of a particle size distribution measured for a filler component using a laser diffraction method.

[0037] In another example, D of the above general formula 1 can also be 50A / D 50C The values ​​are further adjusted to be within a range of 5 or greater, 7 or greater, 10 or greater, 13 or greater, 15 or greater, 17 or greater, 20 or greater, 23 or greater, 25 or greater, 27 or greater, 30 or greater, 32 or greater, 34 or greater, 36 or greater, 38 or greater, 40 or greater, or 42 or greater and / or within a range of 100 or less, 95 or less, 90 or less, 85 or less, 80 or less, 75 or less, 70 or less, 65 or less, 60 or less, 58 or less, 56 or less, 54 or less, 52 or less, 50 or less, 48 ​​or less, 46 or less, or 44 or less.

[0038] As an example, the filler component of the curable composition in the present application may include a filler with at least three different average particle sizes. Such a filler component may show at least three peaks in the volume curve of the particle size distribution measured using a laser diffraction method. In order to make the curable composition solidify into a thermal conductivity showing a level higher than a certain level, it is generally necessary to apply an excessive filler, and according to the present application, even when applied to the curable composition so as to include an excessive filler, the desired hardness and thermal conductivity are also very effectively exerted. However, if the filler is included in excess, there may be a problem in that the viscosity of the curable composition including the filler is significantly increased, but due to the filler component of the present application, the filler with different average particle sizes that can meet the above general formula 1 can be used, even if an excessive filler is applied to the curable composition, the viscosity of the curable composition, etc. can also be maintained at an appropriate level.

[0039] In a specific example, the filler component may include a first filler having an average particle size greater than 40 μm and 200 μm or less, a second filler having an average particle size greater than 5 μm and 40 μm or less, and a third filler having an average particle size of 0.2 μm to 5 μm. The filler component may include three types of fillers, or may include only three types of fillers. In addition, when three types of fillers are included, the first filler may be a filler having the largest average particle size among the fillers included in the filler component, and the third filler may be a filler having the smallest average particle size among the fillers included in the filler component. Therefore, in this case, the average particle size of the first filler may be the maximum average particle size (D 50A ), and the average particle size of the third filler can be the minimum average particle size (D 50C ).

[0040] In another specific example, the volume curve of the particle size distribution measured by the laser diffraction method for the filler component can show a first peak in which the particle size appears in a range of greater than 40 μm and 200 μm or less, a second peak in which the particle size appears in a range of greater than 5 μm and 40 μm or less, and a third peak in which the particle size appears in a range of 0.2 μm to 5 μm. The volume curve of the particle size distribution can include at least three types of peaks, or can only show three types of peaks. In addition, when at least three types of peaks are included, the first peak can be a peak that appears at the maximum particle size in the peak represented by the volume curve, and the third peak can be a peak that appears at the minimum particle size in the peak represented by the volume curve. Therefore, in this case, the particle size at which the first peak appears can be the maximum average particle size (D 50A ), and the particle size at which the third peak appears can be the minimum average particle size (D 50C ).

[0041] In another example, the average particle size of the first filler or the particle size at which the first peak appears can also be adjusted to be within the range of 190 μm or less, 180 μm or less, 170 μm or less, 160 μm or less, 150 μm or less, 140 μm or less, 130 μm or less, 120 μm or less, 115 μm or less, 110 μm or less, 105 μm or less, 100 μm or less, 95 μm or less, 90 μm or less, 85 μm or less, 80 μm or less, or about 75 μm or less and / or within the range of 61 μm or more, 62 μm or more, 63 μm or more, 64 μm or more, 65 μm or more, 66 μm or more, 67 μm or more, 68 μm or more, 69 μm or more, or 70 μm or more.

[0042] In addition, in another example, the average particle size of the second filler or the particle size at which the second peak appears can be adjusted to be greater than about 6 μm, greater than 7 μm, greater than 8 μm, greater than 9 μm, greater than 10 μm, greater than 11 μm, greater than 12 μm, greater than 13 μm, greater than about 14 μm, greater than 15 μm, greater than 16 μm, greater than 17 μm, greater than 18 μm, or greater than 19 μm and / or within the range of 39 μm or less, 38 μm or less. m or less, 37 μm or less, 36 μm or less, 35 μm or less, 34 μm or less, 33 μm or less, 32 μm or less, 31 μm or less, 30 μm or less, 29 μm or less, 28 μm or less, about 27 μm or less, 26 μm or less, 25 μm or less, 24 μm or less, 23 μm or less, 22 μm or less, 21 μm or less, or 20 μm or less.

[0043] Furthermore, in another example, the average particle size of the third filler or the particle size at which the third peak appears can also be adjusted within the range of about 0.3 μm or greater, 0.4 μm or greater, or about 0.5 μm or greater and / or within the range of about 5 μm or less, 4.5 μm or less, about 4 μm or less, about 3.5 μm or less, about 3.3 μm or less, about 3 μm or less, about 2.7 μm or less, about 2.5 μm or less, about 2 μm or less, or about 1.7 μm or less.

[0044] When the filler component includes three types of fillers as above, the ratio (D1 / D2) of the average particle size (D1) of the first filler to the average particle size (D2) of the second filler may be in the range of about 3 to 20. In another example, the ratio (D1 / D2) may be 3.1 or more, 3.2 or more, 3.3 or more, 3.4 or more, or 3.5 or more, or may also be about 19 or less, 18 or less, 17 or less, 16 or less, 15 or less, 14 or less, 13 or less, 12 or less, 11 or less, 10 or less, 9 or less, 8 or less, 7 or less, 6 or less, 5 or less, or 4 or less.

[0045] If the second filler and the third filler having a size within the range are included together with the first filler, and their relationship satisfies the above General Formula 1, etc., high thermal conductivity can be effectively satisfied while maintaining the viscosity of the resin composition at an appropriate level.

[0046] In one example, the curable composition may include a filler component in an amount of 200 parts by weight or more relative to 100 parts by weight of the curable slurry. In another example, the filler component may be included in an amount of 250 parts by weight or more, 300 parts by weight or more, 350 parts by weight or more, 400 parts by weight or more, 450 parts by weight or more, 500 parts by weight or more, 550 parts by weight or more, 600 parts by weight or more, 650 parts by weight or more, or 700 parts by weight or more relative to 100 parts by weight of the curable slurry. The upper limit of the filler component is not significantly limited, but may be 2,000 parts by weight or less, 1,500 parts by weight, 1,000 parts by weight, or 900 parts by weight or less relative to 100 parts by weight of the curable slurry.

[0047] Meanwhile, when the first filler to the third filler are included in the filler component, about 10 to 90 parts by weight of the second filler and about 60 to 140 parts by weight of the third filler may be included relative to 100 parts by weight of the first filler. In another example, the ratio of the second filler relative to 100 parts by weight of the first filler may be about 15 parts by weight or more, about 20 parts by weight or more, about 25 parts by weight or more, about 30 parts by weight or more, about 35 parts by weight or more, about 40 parts by weight or more, about 45 parts by weight or more, or about 47 parts by weight or more, or may be about 85 parts by weight or less, about 80 parts by weight or less, about 75 parts by weight or less, about 70 parts by weight or less, about 65 parts by weight or less, about 60 parts by weight or less, about 55 parts by weight or less, or about 67 parts by weight or less. In another example, the ratio of the third filler can be about 65 parts by weight or more, about 70 parts by weight or more, about 75 parts by weight or more, about 80 parts by weight or more, about 85 parts by weight or more, about 90 parts by weight or more, or about 95 parts by weight or more, or can be about 135 parts by weight or less, about 130 parts by weight or less, about 125 parts by weight or less, about 120 parts by weight or less, about 115 parts by weight or less, about 110 parts by weight or less, or about 105 parts by weight or less.

[0048] As an example, the content of the first filler can be about 10 parts by weight to about 60 parts by weight relative to 100 parts by weight of the total filler components, the content of the second filler can be about 1 part by weight to about 40 parts by weight relative to 100 parts by weight of the total filler components, and the content of the third filler can be about 10 parts by weight to about 60 parts by weight relative to 100 parts by weight of the total filler.

[0049] In one example, the filler component can include a spherical filler in an amount of 30% by weight or more. Generally, if the shape of the filler is spherical, it is not conducive to achieving higher thermal conductivity. That is, with respect to thermal conductivity, it is advantageous to use a non-spherical filler. However, when the filler is non-spherical, it is disadvantageous with respect to the hardness of the cured product, so by including a spherical filler higher than a certain level in the filler component, a favorable effect can be played in terms of the hardness of the cured product. In addition, according to the composition of the present application, even at the content of the spherical filler as described above, high thermal conductivity can also be achieved. In another example, the content of the spherical filler in the filler component can be 35% by weight or more, 40% by weight or more, 45% by weight or more, 50% by weight or more, 55% by weight or more, or 57% by weight or more. Taking into account the thermal conductivity and hardness characteristics of the cured product material, the upper limit of the content of the spherical filler in the filler component can be adjusted within the range of 95 wt % or less, 90 wt % or less, 85 wt % or less, 80 wt % or less, 75 wt % or less, 70 wt % or less, or 65 wt % or less.

[0050] For example, if a non-spherical filler is present in the filler component, it is advantageous to select a filler having a small average particle size as the non-spherical filler. For example, if the filler component contains the first filler to the third filler, a non-spherical filler may be selected as the third filler.

[0051] The term spherical filler is a filler having a sphericity of 0.9 or greater. In another example, the sphericity of the spherical filler may be 0.95 or greater. Therefore, a filler having a sphericity of less than 0.9 is a non-spherical filler.

[0052] Sphericity can be determined by particle shape analysis of the particles. In a specific example, the sphericity of the filler can be defined as the ratio (S' / S) of the surface area (S) of the particle to the surface area (S') of a sphere having the same volume as the particle. For actual particles, circularity is generally used. Circularity can be expressed as the ratio of the boundary (P) of an image obtained from a two-dimensional image of the actual particle to the boundary of a circle having the same area (A) as the area of ​​the same image, and is obtained by the following equation.

[0053] <Circularity equation>

[0054] Circularity = 4πA / P 2

[0055] Circularity is expressed as a value from 0 to 1, with a perfect circle having a value of 1 and more irregularly shaped particles having values ​​less than 1.

[0056] As an example, filler component can be a thermally conductive filler component. As mentioned above, the term thermally conductive filler is a filler component that plays a role in making the curable composition be cured to show a thermal conductivity of about 3.0W / mK or greater. Such filler component can include a filler made of a material having a thermal conductivity of about 1W / mK or greater, 5W / mK or greater, 10W / mK or greater, or about 15W / mK or greater. In another example, the thermal conductivity of the material can be about 400W / mK or less, 350W / mK or less, or about 300W / mK or less. The type of such material is not particularly limited, and it can be exemplified as, for example, ceramic materials such as aluminum oxide (aluminum oxide: Al2O3), aluminum nitride (AlN), boron nitride (BN), silicon nitride (Si3N4), silicon carbide (SiC), beryllium oxide (BeO), zinc oxide (ZnO), magnesium oxide (MgO), or boehmite.

[0057] In addition to such thermally conductive fillers, the filler component may also contain various types of fillers if necessary, and for example, carbon fillers such as graphite, or fillers such as pyrogenic silica, clay, aluminum hydroxide (Al(OH)3), magnesium hydroxide (Mg(OH)2) or calcium carbonate (CaCO3) may be applied.

[0058] In one example, the moisture content (water content) of the filler component can be about 1,000ppm or less. The moisture content can be measured with a Karl Fishcer titrator (KR831) under a relative humidity of 10% and a drift of 5.0 or less. At this point, the moisture content can be the average moisture content of all filler components used in the resin composition. In the present application, filler components that meet the above conditions can also be selectively used, or the water content of the filler can also be adjusted by drying the filler component to be used in an oven at a temperature of about 200°C to meet the above moisture content range. In another example, the upper limit of the moisture content of the filler component can be about 800ppm or less, 600ppm or less, or about 400ppm or less, and its lower limit can be about 100ppm or more, or about 200ppm or more.

[0059] In one example, the curable composition may include a reducing agent in the range of 0.05 to 6 parts by weight relative to 100 parts by weight of the curable slurry, which is not limited thereto, but as an example, the lower limit of the reducing agent content may be 0.1 parts by weight or more, 0.3 parts by weight or more, 0.5 parts by weight or more, 0.7 parts by weight or more, 1 part by weight or more, 1.3 parts by weight or more, 1.5 parts by weight or more, 1.7 parts by weight or more, 2 parts by weight or more, 2.3 parts by weight or more, 2.5 parts by weight or more, 2.7 parts by weight or more, 3 parts by weight or more, or 3.2 parts by weight or more, and the upper limit thereof may be 6 parts by weight or less, 5.5 parts by weight or less, 5 parts by weight or less, 4.5 parts by weight or less, 4 parts by weight or less, or 3.5 parts by weight or less. By including the reducing agent in the above-mentioned content, the present invention may obtain a cured product that ensures sufficient curability to have desired physical properties.

[0060] In addition, in one example, the reducing agent may include a metal compound. According to the present invention, the metal compound is not significantly limited, as long as the layer of the curable composition and the layer of the initiator component are in direct contact with each other to initiate or promote the redox reaction without separate heat or UV irradiation, and the composition containing the reducing agent can be stably stored, and it is particularly preferred to have excellent solubility, compatibility, dispersion rate and reactivity with the curable slurry.

[0061] The metal compound may be included in any one of the layers of the initiator component and the curable composition in the film in an effective amount. Here, the effective amount means the amount capable of initiating a significant oxidation-reduction reaction to produce a cured product. That is, the metal compound may be included in any one of the layers of the initiator component and the curable composition in an effective amount, and may not be substantially included in another layer. As an example, when the metal compound is included in the layer of the initiator component in an effective amount, the metal compound may not be substantially included in the layer of the curable composition. In addition, as another example, when the metal compound is included in the layer of the curable composition in an effective amount, the metal compound may not be substantially included in the layer of the initiator component. Here, the meaning of being substantially not included may be the meaning of being included in 0 wt %, and even if the metal compound is included in the layer of the curable composition, it is also included in 1 wt % or less, 0.5 wt % or less, or 0.1 wt % or less, so that it may be included in a trace amount rather than an effective amount capable of initiating an oxidation-reduction reaction.

[0062] In addition, in the layer of the initiator component in the film and the layer of the curable composition, the layer containing the metal compound in an effective amount may not substantially contain an oxidant. That is, in the present invention, it is not possible to adopt the situation that the oxidant and the metal compound are substantially contained in the same layer at the same time before forming the cured product. In other words, when the metal compound is contained in the layer of the initiator component in the film in an effective amount, the oxidant may not be contained in the layer of the initiator component in the film in an effective amount, but may be contained in the layer of the curable composition in an effective amount. As another example, when the metal compound is contained in the layer of the curable composition in an effective amount, the oxidant may not be contained in the layer of the curable composition in an effective amount, but may be contained in the layer of the initiator component of the film in an effective amount.

[0063] As an example, the metal contained in the metal compound can be a transition metal, and the metal compound can be a salt or chelate containing metal ions or a hydrate thereof, and can include one or more types. Here, the metal ion can be selected from cobalt, iron, vanadium, copper, manganese, nickel, titanium, aluminum, tin, chromium, zinc, zirconium, indium, manganese, and one or more of their mixtures. In detail, the metal compound can be a cobalt-containing component, wherein in the cobalt-containing component, cobalt can have an oxidation state of +2 valence or +3 valence. Available cobalt-containing components can include cobalt naphthenate, cobalt sulfide, etc., but are not limited thereto. As another example, the metal compound can be an iron-containing component, wherein in the iron-containing component, iron can have an oxidation state of +2 valence or +3 valence. Available iron-containing components can include iron sulfate (III), iron sulfate (II), iron chloride (III), iron chloride (II), iron carboxylate, iron naphthenate, iron (III), iron (II) or iron acetylacetonate (III), but are not limited thereto. As another example, the metal compound can be a vanadium-containing component, wherein in the vanadium-containing component, vanadium can have an oxidation state of +4 or +5 valences. Available vanadium-containing components can include vanadium acetylacetonate, vanadium stearate, vanadium naphthenate, vanadium benzoyl acetonate, vanadium oxalate, triisopropoxide vanadium (V), ammonium metavanadate (V), sodium metavanadate, vanadium pentoxide (V) or vanadium sulfate (V), but is not limited thereto. As another example, the metal compound can be a copper-containing component, wherein in the copper-containing component, copper can have an oxidation state of +1 or +2 valences. Available copper-containing components can include a complex of copper acetate, copper chloride, copper benzoate, copper acetone, copper naphthenate, copper carboxylate, copper salicylate, copper and thiourea or ethylenediaminetetraacetic acid, but is not limited thereto. In addition, the metal compound can be exemplified as manganese naphthenate, nickel naphthenate, titanium acetylacetonate, copper sulfate, manganese sulfate or nickel sulfate, etc. Furthermore, the reducing agent may include an organic compound, wherein the organic compound is not significantly limited as long as it initiates or promotes an oxidation-reduction reaction by directly contacting a layer of the curable composition with a layer of the initiator component without separate heat or UV irradiation.

[0064] The organic compound may also be substantially contained together in the layer containing the initiator component and the layer containing the oxidant in the layer of the curable composition in the film, and may also be substantially contained together in the layer containing the metal compound, but may be selectively and substantially contained only in the layer containing the oxidant or the layer containing the metal compound.

[0065] As an example, the organic compound may be at least one of the group consisting of amine, pyridine, aldehyde amine condensation compound, thiourea and derivatives thereof, and may also be two or more. In detail, examples of organic compounds may include N, N-dimethyl-p-toluidine, N, N-dimethylformamide, triethylamine, N, N-diisopropyl alcohol p-chloroaniline, N, N-diisopropyl alcohol p-bromoaniline, N, N-diisopropyl alcohol p-bromo-o-methylaniline, N, N-dimethyl-p-chloroaniline, N, N-dimethyl-p-bromoaniline, N, N-diethyl-p-chloroaniline, N, N-diethyl-p-bromoaniline, 3, 5-diethyl-1, 2-dihydro-1-phenyl-2-propylpyridine, N-benzoylthiourea or tetramethylthiourea, etc., but are not limited thereto, and preferably, tertiary amine-based organic compounds may be used. In particular, the organic compound is preferably a compound in a liquid phase and having a half-life in the range of 70°C to 170°C or in the range of 80°C to 150°C. By using an organic compound whose half-life temperature satisfies the above range, the present invention can suppress self-reaction in a storage state, and can maintain the viscosity of the composition containing the organic compound at a desired level in the present invention. In this specification, the half-life is an index showing the decomposition rate of a compound, which means the time until the remaining amount of the compound is halved.

[0066] In an example, when reducing agent comprises metallic compound and organic compound, relative to the metallic compound of 100 weight parts, organic compound can be included in the scope of 5 weight parts to 50 weight parts, and as an example, its lower limit can be 6 weight parts or more, 7 weight parts or more, 8 weight parts or more, 9 weight parts or more, 10 weight parts or more, 11 weight parts or more, 12 weight parts or more, 13 weight parts or more, 14 weight parts or more, 15 weight parts or more, 16 weight parts or more, 17 weight parts or more, 18 weight parts or more, 19 weight parts or more, 20 weight parts or more or 21 weight parts or more, and its upper limit can be 45 weight parts or less, 43 weight parts or less, 40 weight parts or less, 37 weight parts or less, 35 weight parts or less, 30 weight parts or less, 27 weight parts or less, 25 weight parts or less or 23 weight parts or less.By comprising metallic compound and organic compound via enough curing rate with above weight ratio, the present invention can provide the cured product with excellent curing physical properties.

[0067] In addition, in one example, the curable composition may include an oxidant, wherein the oxidant is not significantly limited as long as it participates in an oxidation-reduction reaction to generate free radicals that initiate polymerization, and in particular, it is preferred that it has excellent compatibility with the curable slurry. As an example, the oxidant may include peroxides, peroxyesters, diacyl peroxides, or persulfates, but is not limited thereto, and specifically, as the oxidant, methyl ethyl ketone peroxide, tert-butyl hydroperoxide, p-menthane hydroperoxide, cumene hydroperoxide, diisopropylbenzene hydroperoxide, tert-butyl peroxylaurate, tert-butyl peroxybenzoate, tert-butyl peroxydecanoate, 1,5-di-tert-butylperoxy-3,3,5-trimethylcyclohexane, ethyl acetoacetate peroxide, benzoyl peroxide, hydrogen peroxide, or a combination thereof may be used.

[0068] In one example, the oxidizing agent may be included in the range of 30 to 100 parts by weight relative to 100 parts by weight of the reducing agent, and as an example, the lower limit thereof may be 35 parts by weight or more, 37 parts by weight or more, 40 parts by weight or more, 43 parts by weight or more, 45 parts by weight or more, 47 parts by weight or more, 50 parts by weight or more, 53 parts by weight or more, 55 parts by weight or more, or 57 parts by weight or more, and the upper limit thereof may be 95 parts by weight or less, 93 parts by weight or less, 90 parts by weight or less, 87 parts by weight or less, 85 parts by weight or less, 83 parts by weight or less, 80 parts by weight or less, 77 parts by weight or less, 75 parts by weight or less, 73 parts by weight or less, 70 parts by weight or less, 67 parts by weight or less, 65 parts by weight or less, or 63 parts by weight or less.

[0069] In a specific example, as described above, the curable slurry can be a polymer component. In particular, the layer of the curable composition in the present application can include a curable slurry together with a large amount of filler components. Therefore, as described below, by combining the curable slurry with a specific component with a large amount of filler components, the present application can have excellent properties in terms of the compatibility between the mixing characteristics and a large amount of filler components and the curable slurry.

[0070] The curable composition may include the curable syrup in an amount of 6 wt % to 20 wt %, but is not limited thereto, but as an example, the lower limit of the curable syrup may be 6 wt % or more, 6.5 wt % or more, 7 wt % or more, 7.5 wt % or more, 8 wt % or more, 8.5 wt % or more, 9 wt % or more, 9.5 wt % or more, or 10 wt % or more, and the upper limit thereof may be 19 wt % or less, 18 wt % or less, 17 wt % or less, 16 wt % or less, 15 wt % or less, 14 wt % or less, 13 wt % or less, or 12 wt % or less.

[0071] In one example, the curable syrup may include an alkyl (meth)acrylate unit, a monomer unit containing a polar functional group, and a crosslinking agent. As an example, the alkyl (meth)acrylate unit may be an alkyl (meth)acrylate having an alkyl group containing 4 to 20 carbon atoms, wherein the carbon number of the alkyl group may be, for example, 16 or less, 12 or less, or 8 or less. Such an alkyl (meth)acrylate may be included in the curable syrup in an amount of about 1 wt % to 12 wt %. In another example, the upper limit of the ratio may be 1.5 weight % or more, 2 weight % or more, 2.5 weight % or more, 3 weight % or more, 3.5 weight % or more, 4 weight % or more, 4.5 weight % or more, 5.5 weight % or more, or 5.7 weight % or more, and the lower limit thereof may be 11.5 weight % or less, 11 weight % or less, 10.5 weight % or less, 10 weight % or less, 9.5 weight % or less, 9 weight % or less, 8.5 weight % or less, 8 weight % or less, 7.5 weight % or less, 7 weight % or less, or 6.5 or less.

[0072] In addition, the alkyl group in the (meth)acrylic acid alkyl ester unit may be a linear or branched aliphatic alkyl group, and may be in a substituted or unsubstituted state. As the linear or branched aliphatic (meth)acrylic acid alkyl ester, for example, any one or two or more selected from the following groups may be used: n-butyl (meth)acrylate, tert-butyl (meth)acrylate, sec-butyl (meth)acrylate, amyl (meth)acrylate, 2-ethylbutyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, lauryl (meth)acrylate, and tetradecyl (meth)acrylate.

[0073] The curable syrup may include a polar functional group-containing monomer unit as an additional component. The curable syrup may include a hydroxyl group-containing monomer unit, a carboxyl group-containing monomer unit, or an epoxy group-containing monomer unit as the polar functional group-containing monomer unit, but is not limited thereto.

[0074] As the monomer having a polar functional group, for example, hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate and / or 8-hydroxyoctyl (meth)acrylate (wherein the carbon number of the alkyl group may be 1 to 20, 1 to 16, 1 to 12, 1 to 8 or 1 to 4, and the alkyl group may be linear or branched, or may be substituted or unsubstituted); or hydroxypolyalkylene glycol (meth)acrylates such as 2-hydroxypolyethylene glycol (meth)acrylate or 2-hydroxypolypropylene glycol (meth)acrylate, etc.; epoxy-containing (meth)acrylates such as glycidyl (meth)acrylate); or acrylic acid, etc. may be used, without being limited thereto.

[0075] In one embodiment of the present application, the monomer unit having a polar functional group may be included in an amount of 500 parts by weight or more, relative to 100 parts by weight of the (meth)acrylic acid alkyl ester unit, and in another example, the lower limit thereof may be 600 parts by weight or more, 700 parts by weight or more, 800 parts by weight or more, 900 parts by weight or more, 1,000 parts by weight or more, 1,100 parts by weight or more, 1,200 parts by weight or more, 1,300 parts by weight or more, 1,350 parts by weight or more, 1,400 parts by weight or more, or 1,450 parts by weight or more, and the upper limit thereof may be 3,000 parts by weight or less, 2,500 parts by weight or less, 2,000 parts by weight or less, or 1,700 parts by weight or less.

[0076] Although not limited thereto, in one embodiment of the present application, the curable syrup may contain a hydroxyl-containing monomer unit and an epoxy-containing monomer unit as the polar functional group-containing monomer unit, wherein the hydroxyl-containing monomer unit (M OH ) and epoxy-containing monomer units (M E ) ratio (M OH / M E ) can be in the range of 0.1 to 10, and its upper limit can be 0.3 or more, 0.5 or more, 0.7 or more, 1 or more, 1.3 or more, 1.5 or more, 1.7 or more, 2 or more, 2.3 or more, 2.5 or more, 2.7 or more, or 3 or more, and its lower limit can be 9 or less, 8 or less, 7 or less, 6 or less, 5 or less, 4 or less, 3.7 or less, 3.5 or less, or 3.3 or less.

[0077] Furthermore, the curable syrup of the present invention may further contain monomer units other than the foregoing, if necessary.

[0078] For example, the curable slurry may also include nitrogen-containing reactive monomer units. Such nitrogen-containing reactive monomers may be exemplified by one or two or more of the following: (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, N-methylol(meth)acrylamide, diacetone(meth)acrylamide, N-vinyl acetamide, N,N'-methylenebis(meth)acrylamide, N,N-dimethylaminopropyl(meth)acrylamide, N,N-dimethylaminopropyl(meth)acrylamide, N-vinyl pyrrolidone, N-vinyl caprolactam or (meth)acryloylmorpholine, but are not limited thereto. Suitable monomers may be exemplified by, for example, (meth)acrylamide, N-alkyl(meth)acrylamide and / or N,N-dialkyl(meth)acrylamide, etc. Here, the alkyl group may be exemplified by a linear, branched or cyclic substituted or unsubstituted alkyl group having 1 to 20 carbon atoms, 1 to 16 carbon atoms, 1 to 12 carbon atoms, 1 to 8 carbon atoms, or 1 to 4 carbon atoms.

[0079] If necessary, the curable composition according to one example of the present application may further include a crosslinking agent, which may form a cured product having appropriate adhesion and hardness by realizing a crosslinking structure with the components included in the curable syrup.

[0080] As a crosslinking agent, for example, an acrylate crosslinking agent based on carbamate, an aliphatic isocyanate crosslinking agent, an epoxy crosslinking agent, an aziridine crosslinking agent and a metal chelate crosslinking agent can be used, without being limited thereto. In addition, as a crosslinking agent, one or two or more types can be used. The acrylate crosslinking agent based on carbamate is a compound having a plurality of carbamate bonds (-NHCOO-) in its molecular chain and having an acrylic group capable of reacting with ultraviolet rays at the molecular end, and commercial PU330 (Miwon Commercial), PU256 (Miwon Commercial), PU610 (Miwon Commercial) and PU340 (Miwon Commercial) etc. can be used. The aliphatic isocyanate crosslinking agent is, for example, an isocyanate compound such as isophorone diisocyanate, methylene dicyclohexyl diisocyanate or cyclohexane diisocyanate, but derivatives thereof such as dimers or trimers can also be used. As epoxy crosslinking agents, for example, ethylene glycol diglycidyl ether, triglycidyl ether, trimethylolpropane triglycidyl ether, N,N,N',N'-tetraglycidylethylenediamine or glycerol diglycidyl ether can be used. As aziridine crosslinking agents, for example, N,N'-toluene-2,4-bis(1-aziridine carboxamide), N,N'-diphenylmethane-4,4'-bis(1-aziridine carboxamide), triethylene melamine, bisisophthaloyl-1-(2-methylaziridine) or tri-1-aziridine phosphine oxide can be used. As metal chelate crosslinking agents, for example, metal chelate components can be used, which are compounds in which a polyvalent metal (e.g., aluminum, iron, zinc, tin, titanium, antimony, magnesium and / or vanadium) is coordinated with acetylacetone or ethyl acetoacetate.

[0081] The method of preparing the curable syrup containing such units is not particularly limited. For example, in order to achieve the above-mentioned syrup composition, the curable syrup can be formed by mixing monomers at a desired ratio and then appropriately partially polymerizing the mixture.

[0082] According to the present invention, a cured product with the desired physical properties of the present invention can be produced only by contacting the layer of the curable composition with the layer of the initiator component in the film of the layer including the initiator component on the surface as described above. That is, the application can provide a cured product with desired hardness and physical properties without the need for separate heat or UV irradiation, because the curing reaction starts at room temperature and is carried out at room temperature. However, the irradiation step of heat or UV can also be added as needed. Curing can be carried out by the redox polymerization reaction between the initiator component of the curable composition and the initiator component present on the surface of the film.

[0083] When layers having different components are in contact with each other and the metal compound diffuses into the contact layer, thereby initiating an oxidation-reduction reaction, a cured product of the present invention can be produced, wherein if the curing reaction proceeds too quickly, the metal compound, etc. cannot be sufficiently diffused, and thus a cross-linking reaction is difficult to occur between the curable slurries, so that the cured product may not have uniform physical properties. Therefore, by having such a composition, the present invention can control the curing reaction rate of the curable composition to an appropriate level according to the above production method.

[0084] In the present invention, curable composition can be solvent-free composition. Here, solvent-free composition is a composition substantially free of solvent (aqueous solvent and organic solvent). Therefore, the content of aqueous solvent and organic solvent in curable composition can be 1 wt % or less, 0.5 wt % or less, 0.1 wt % or less, or can be substantially 0 wt %. That is, curable composition of the present invention is realized to have such composition, so that it can realize physical properties equal to or better than the physical properties of solvent-based while being solvent-free, and can be applicable to inert redox system at the same time.

[0085] In addition, the viscosity of the curable composition in the present invention measured at a temperature of 25° C. and a shear rate of 1 rpm may be in the range of 10,000 cps to 30,000 cps, 15,000 cps to 25,000 cps, 17,000 cps to 23,000 cps, or 18,000 cps to 22,000 cps. The viscosity may be measured at room temperature in a Brookfield HB viscometer using a No. 63 spindle.

[0086] The cured product according to the present application may have thermal conductivity, and specifically, the thermal conductivity of the cured product may be 0.1 W / mK or more. It is not limited thereto, but as an example, the thermal conductivity of the cured product may also be about 50 W / mK or less, 45 W / mk or less, 40 W / mk or less, 35 W / mk or less, 30 W / mk or less, 25 W / mk or less, 20 W / mK or less, 15 W / mK or less, about 10 W / mK or less, 9 W / mK or less, 8 W / mK or less, 7 W / mK or less, 6 W / mK or less, 5 W / mK or less, or about 4 W / mK or less. The thermal conductivity of the cured product may be measured, for example, according to ASTM D5470 standard or ISO 22007-2 standard.

[0087] In one example, the cured product according to the present application can be used as a battery module housing or a battery cell due to the above thermal conductivity, and the heat generated inside the battery module can be effectively evacuated to the outside. The battery cell can be housed in a module housing, one or more battery cells can be present in the module housing, and a plurality of battery cells can be housed in the module housing. The type of battery cell housed in the module housing is not particularly limited, and all known various battery cells can be applied. In one example, the battery cell can be a bag type. Figure 1 and Figure 2 1 is a schematic diagram of a module housing 10 containing a battery cell 20 as viewed from the top. The exemplary module housing 10 may be in the form of a box including a lower plate 10a and a plurality of side walls 10b, and may further include an upper plate 10c that seals the internal space. The film 30 may be in the form of a relatively thin layer (see Figure 2 ), or may be in the form of filling the inner space of the housing 10. Figure 2 As shown, in at least one surface inside the module housing 10 , for example, in the surface 10 a in contact with the film 30 , there may be a guide portion 10 d capable of guiding the accommodated battery cell 20 .

[0088] In another specific example according to the present invention, the present invention may relate to a method for producing a cured product. The method for producing a cured product may include a step of contacting a layer of a curable composition comprising a curable slurry component, a filler component and an initiator component with a layer of an initiator component of a film comprising a layer of an initiator component on a surface thereof.

[0089] The method of bringing the layer of the curable composition into contact with the layer of the initiator component of the film including the layer of the initiator component on the surface is not significantly limited, but as an example, the curable composition may be directly applied to the film, or may also be applied to any substrate and then laminated. In addition, when bringing the layer of the initiator component of the film including the layer of the initiator component on the surface into contact with the layer of the curable composition, the layer of the initiator component of the film including the layer of the initiator component on the surface may also be brought into contact with one side or both sides of the layer of the curable composition.

[0090] Regarding the respective configurations, the contents described above apply in the same manner.

[0091] Beneficial Effects

[0092] According to an example of the present invention, by using a one-component curing method rather than a two-component curing method in which a main agent and a curing agent are separated and mixed and then applied, a film having excellent storage characteristics and capable of curing without separate UV or heat even under reaction conditions at room temperature and in darkness can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0093] Figure 1 and Figure 2 Schematic diagram of a module housing containing battery cells, viewed from the top. DETAILED DESCRIPTION

[0094] Hereinafter, preferred experimental examples are presented to help understand the present invention. However, the following experimental examples are only intended to help understand the present invention, and the present invention is not limited to the following experimental examples.

[0095] Preparation of free radical polymer (P)

[0096] 2-Ethylhexyl acrylate (2-EHA) and 2-hydroxyethyl acrylate (HEA) were added to a flask equipped with a mechanical stirrer at a weight ratio of 60:40 (2-EHA:HEA). A solution in which Irgacure 184 as a photoinitiator and ethyl acetate (EAC) were diluted at a ratio of 1:1 in an amount of about 0.1 wt % relative to the total weight of the compounds added to the flask was further added thereto, and then nitrogen was introduced therein under normal pressure conditions, the temperature was raised to about 60° C., and the mixture was irradiated with a metal halide lamp while stirring, and the nitrogen introduction and lamp irradiation were stopped once the temperature reached 68° C., thereby obtaining a free radical polymer (P) (solid content: about 12%).

[0097] At this time, the prepared free radical polymer (P) had a viscosity of about 26,830 cps measured by Brookfield's DV-3 using a No. 63 rotor at a temperature of 25° C. and a torque of 31.6%, a weight average molecular weight (Mw) of about 2,192,000 g / mol, and a polydispersity index (PDI) of about 3.08.

[0098] Preparation Example 1: Preparation of curable composition

[0099] The above-prepared free radical polymer (P), 2-hydroxyethyl acrylate (2-HEA) and glycidyl methacrylate (GMA) were used as the curable syrup, and a multifunctional aliphatic urethane acrylate (SUO-1020 of SHIN-AT&C) was used as the crosslinking agent (H), and a phosphorus-based flame retardant (FR-119L of Chempia) was used as the flame retardant (N), a modified polyester dispersant (Disperbyk-111 of BYK) was used as the dispersant (D), a filler component (F), and a methyl ethyl ketone as the oxidant (O) was used to prepare the syrup. Oxide (MEKP) and N,N-dimethyl-p-toluidine (DMPT) as an organic compound (A), these materials are added to a paste mixer at a weight ratio of about 1.17:7.48:2.49:0.59:1.76:0.1:86.05:0.23:0.07 (P:2-HEA:GMA:H:N:D:F:O:A) and fully stirred to prepare a curable composition, the viscosity of the curable composition being about 200,000 cps as measured by Brookfield's DV-3 at room temperature of 25°C and a shear rate of 1 rpm.

[0100] As the filler component (F), spherical alumina having an average particle size of about 70 μm (BAK-70 of Bestrytech, sphericity of 0.95 or more), aluminum hydroxide having an average particle size of about 20 μm (DH-50P of Korea Alumina, sphericity of 0.95 or more), and rectangular alumina having an average particle size of about 1.6 μm (KLS-51 of Korea Alumina, sphericity of less than 0.9) were mixed and used in a weight ratio of about 34.42:17.21:34.42.

[0101] Preparation Example 2: Preparation of curable composition

[0102] By using the above-prepared free radical polymer (P), 2-hydroxyethyl acrylate (2-HEA) and glycidyl methacrylate (GMA) as a curable syrup, and a multifunctional aliphatic urethane acrylate (SHIN-A) as a crosslinking agent (H), T&C's SUO-1020), and using a phosphorus-based flame retardant (Chempia's FR-119L) as a flame retardant (N), a modified polyester dispersant (BYK's Disperbyk-111) as a dispersant (D), a filler component (F), methyl ethyl ketone peroxide (MEKP) as an oxidant (O) and N,N-dimethyl-p-toluidine (DMPT) as an organic compound (A), these materials are added to a pulp mixer in a weight ratio of about 0.5:3.7:1.2:0.48:1.71:0.1:92.05:0.2:0.06 (P:2-HEA:GMA:H:N:D:F:O:A) and fully stirred.

[0103] As the filler component (F), spherical alumina having an average particle size of about 70 μm (BAK-70 of Bestrytech, sphericity of 0.95 or more), aluminum hydroxide having an average particle size of about 20 μm (DH-50P of Korea Alumina, sphericity of 0.95 or more), and rectangular alumina having an average particle size of about 1.6 μm (KLS-51 of Korea Alumina, sphericity of less than 0.9) were mixed and used in a weight ratio of about 36.82:18.41:36.82.

[0104] Example 1

[0105] A metal compound solution was prepared by diluting iron (III) acetylacetonate as the metal compound (M) in toluene to 15% by weight.

[0106] Then, after the metal compound solutions were each applied on an aluminum foil so that the weight ratio of the oxidant, the organic compound and the metal compound in the curable composition according to Preparation Example 1 was about 0.23:0.07:0.32 (O:A:M), it was dried at about 25°C for 5 minutes and then dried on a hot plate at 100°C for 5 minutes to produce a film including an activation layer.

[0107] The curable composition prepared above was applied to contact the metal compound of the activation layer, thereby producing a cured product. At this time, the curable composition was applied to a thickness of 1T.

[0108] Example 2

[0109] A metal compound solution was prepared by diluting iron (III) acetylacetonate as the metal compound (M) in toluene to 15% by weight.

[0110] Then, after the metal compound solutions were each applied on a PET film so that the weight ratio of the oxidant, the organic compound and the metal compound in the curable composition according to Preparation Example 1 was about 0.23:0.07:0.32 (O:A:M), it was dried at about 25°C for 5 minutes and then dried on a hot plate at 100°C for 5 minutes to produce a film including an activation layer.

[0111] The curable composition prepared above was applied to contact the metal compound of the activation layer, thereby producing a cured product. At this time, the curable composition was applied to a thickness of 1T.

[0112] Comparative Example 1

[0113] A metal compound solution was prepared by diluting iron (III) acetylacetonate as the metal compound (M) in toluene to 15% by weight.

[0114] Then, the metal compound solution was mixed with the curable composition prepared above and stirred sufficiently so that in the curable composition according to Preparation Example 1, the weight ratio of the oxidant, the organic compound and the metal compound was about 0.23:0.07:0.64 (O:A:M).

[0115] The mixture was applied to an aluminum foil to a thickness of 2T and a PET film was placed on top.

[0116] Comparative Example 2

[0117] The curable composition prepared above was applied on an aluminum foil to a thickness of 1T in the same manner as in Example 1 without applying the metal compound solution.

[0118] Comparative Example 3

[0119] After the metal compound solution and the curable composition prepared above were mixed together and applied on an aluminum foil to a thickness of about 1T without applying the metal compound solution on the aluminum foil so that the weight ratio of the oxidant, the organic compound and the metal compound in the curable composition according to Preparation Example 1 was about 0.23:0.07:0.32 (O:A:M), it was dried at about 25°C for 5 minutes and then dried on a hot plate at 100°C for 5 minutes to produce a film including an activation layer.

[0120] Comparative Example 4

[0121] This was prepared in the same manner as in Example 1, except that the curable composition according to Preparation Example 2 was used.

[0122] In this case, the compatibility between the curable slurry and the filler component is reduced, thereby causing a cracking phenomenon and failing to formulate.

[0123] Experimental Example 1: Hardness

[0124] The PET film attached to each of the cured products produced by Examples and Comparative Examples was removed, and for the side from which the PET film was removed from the cured product, the hardness was measured using a durometer Shore A durometer at a temperature of about 25° C. The hardness value represents an average value after 3-point measurement.

[0125] Experimental Example 2: Total mass loss (TML)

[0126] The total mass loss was evaluated in the following manner. A sample having a thickness of about 2T was prepared by removing the PET film attached to each of the cured products produced by the embodiments and comparative examples and cutting it into an aluminum disk suitable for a diameter of about 5 cm, and the weight (A, unit: g) of the sample was measured. Thereafter, immediately after the sample was placed at 150° C. for 45 minutes, the weight (B, unit: g) of the sample was measured, and TML was calculated according to the following general formula 2. In the following, C is the weight (unit: g) of the aluminum attached to the cured product.

[0127] [General formula 2]

[0128] Total mass loss (TML, unit: %) = (AB) / (AC) × 100 The following Table 1 summarizes the results according to the above experimental examples.

[0129] [Table 1]

[0130] Hardness (HS) Total mass loss (%) Example 1 93 0.98 Example 2 92 1.02 Comparative Example 1 91 1.11 Comparative Example 2 Uncured 10.89 Comparative Example 3 91 1.11

Claims

1. A film comprising a substrate and an activation layer comprising an initiator component on the surface of the substrate, wherein When a layer of a curable composition comprising a curable syrup, a filler component and an initiator component is brought into contact with the initiator component of the film, a curing reaction is performed, and The initiator component is an inert redox initiator system comprising an oxidizing agent and a reducing agent, wherein the reducing agent comprises a metal compound, and the metal compound is contained in an effective amount only in any one of the activating layer and the layer of the curable composition of the film.

2. The film according to claim 1, wherein The substrate includes polymers, plastics, metals, wood, leather or concrete.

3. The film according to claim 1, wherein The curable composition includes the filler component in an amount of 200 parts by weight or more relative to 100 parts by weight of the curable syrup.

4. The film according to claim 1, wherein The filler component includes two or more types of fillers having average particle sizes different from each other, and the cured product satisfies the following General Formula 1: [General formula 1] 5≤D 50A / D 50C ≤100 in, D 50A is the maximum average particle size of the filler in the filler component, and D 50C It is the minimum average particle size of the filler in the filler component.

5. The film according to claim 1, wherein The filler component contains three types of fillers having average particle sizes different from each other.

6. The film according to claim 1, wherein The filler component includes: a first filler having an average particle size greater than 40 μm and 200 μm or less; a second filler having an average particle size greater than 5 μm and 40 μm or less; and a third filler having an average particle size ranging from 0.2 μm to 5 μm.

7. The film according to claim 1, wherein The filler component includes fumed silica, clay, calcium carbonate (CaCO3), aluminum oxide (Al2O3), aluminum nitride (AlN), boron nitride (BN), silicon nitride (Si3N4), silicon carbide (SiC), beryllium oxide (BeO), zinc oxide (ZnO), aluminum hydroxide (Al(OH)3), boehmite, magnesium oxide (MgO), magnesium hydroxide (Mg(OH)2), or carbon filler as filler.

8. The film according to claim 1, wherein The curable composition includes the reducing agent in a range of 0.05 parts by weight to 6 parts by weight relative to 100 parts by weight of the curable syrup.

9. The film according to claim 1, wherein The metal compound is a salt or chelate containing a metal ion, or a hydrate thereof, and the metal ion is selected from cobalt, iron, vanadium, copper, manganese, nickel, titanium, aluminum, tin, chromium, zinc, zirconium, indium, manganese and a mixture thereof.

10. The film of claim 1, wherein The reducing agent further comprises at least one organic compound selected from the group consisting of amines, pyridine, aldehyde-amine condensation compounds, thiourea and derivatives thereof.

11. The film according to claim 10, wherein The organic compound is included in an amount ranging from 5 parts by weight to 50 parts by weight relative to 100 parts by weight of the metal compound.

12. The film of claim 1, wherein The oxidizing agent includes peroxides, peroxyesters, diacyl peroxides or persulfates.

13. The film of claim 1, wherein The oxidizing agent is included in an amount ranging from 30 parts by weight to 100 parts by weight relative to 100 parts by weight of the reducing agent.

14. The film of claim 1, wherein The curable composition includes the curable syrup in an amount of 6 wt % to 20 wt %.

15. The film of claim 1, wherein The curable syrup comprises an alkyl (meth)acrylate unit, a monomer unit containing a polar functional group, and a cross-linking agent.

16. The film according to claim 15, wherein The polar functional group includes a hydroxyl group, an epoxy group, an isocyanate group, a glycidyl group, an alkenyloxycarbonyl group, a (meth)acryloyl group or an alkenyloxyalkyl group.

17. The film of claim 15, wherein The curable syrup includes the alkyl (meth)acrylate unit in an amount of 1 wt % to 12 wt %.

18. The film of claim 15, wherein The curable syrup includes the polar functional group-containing monomer unit in an amount of 500 parts by weight or more relative to 100 parts by weight of the alkyl (meth)acrylate unit.

19. The film of claim 15, wherein The curable syrup includes a hydroxyl group-containing monomer unit and an epoxy group-containing monomer unit as the polar functional group-containing monomer unit.

20. The film of claim 15, wherein The cross-linking agent includes a multifunctional acrylate compound, a multifunctional isocyanate compound or a urethane acrylate compound.

21. The film of claim 1, wherein The curable composition is solvent-free.

22. The film of claim 1, wherein The curable composition has a viscosity ranging from 10,000 cps to 25,000 cps measured at a temperature of 25° C. and a shear rate of 1 rpm.

23. A method for producing a cured product comprising the step of contacting a layer of a curable composition comprising a curable syrup component, a filler component and an initiator component with the layer of the initiator component of the film according to claim 1.

24. The method for producing a cured product according to claim 23, comprising: A step of bringing the layer of the initiator component of the film including the layer of the initiator component on the surface into contact with both sides of the layer of the curable composition.

25. The method for producing a cured product according to claim 23, wherein The curing reaction proceeds at room temperature through the contacting step.

26. The method for producing a cured product according to claim 25, wherein The curing reaction proceeds through a redox polymerization reaction of the initiator component of the curable composition with the initiator component present in the activation layer of the film.